Ework and ebusiness in architecture, engineering and construction : proceedings of the 10th European Conference on Product and Process Modelling (ECPPM 2014), Vienna Austria, 17-19 September 2014 /: proceedings of the 10th European Conference on Product and Process Modelling (ECPPM 2014), Vienna Austria, 17-19 September 2014. ([2015]) - Unknown
No abstract available